Revision Hip Arthroplasty Through a Gluteal-Sparing Extended Posterior Approach May be Able to Achieve Similar Functional Outcomes to Primary Hip Arthroplasty - Dominic Thewlis, PhD; Jasvir Bahl, PhD; Hao Wei (Harvey) Chai, MBBS; Stuart A. Callary, PhD; Thomas M. Grace, PhD; John B. Arnold, PhD; Mark Taylor, PhD; Lucian B. Solomon, MD, FRCAS, PhD (Arthroplasty Today, 2025)
Background: Revision total hip arthroplasty (THA) has been reported to have worse outcomes when compared to primary procedures, which may, in part, be due to the increased exposure required for the procedure. We aimed to investigate the postoperative functional outcomes of 2 groups of primary and revision THA, when revision procedures were performed using a gluteal-sparing extended posterior approach. Methods: Two groups of 51 primary and 21 revision THAs were prospectively recruited from a single center between 2016 and 2019. Both groups were assessed preoperatively using quantitative gait analysis and patient-reported outcomes, and at 3 and 12 months postoperatively. Hip and knee kinematics were computed from motion capture data acquired at the gait analysis. Kinematic and patient-reported outcome measures data were analyzed using linear mixed models. Statistical parametric analysis complemented the main analysis of the kinematics. Results: Patients in the primary group had worse preoperative patient-reported outcome measures when compared to the revision group. There were no between-group differences in walking speed. Hip extension in late stance phase of gait was 9° and 5° lower for the revision group when compared to the primary group at 3 and 12 months, respectively. These differences were not statistically significant, but the magnitude of the effect size was noteworthy suggesting a functional deficit (Cohen’s d = 0.64 and 0.54, respectively). Conclusions: Revision THA using a gluteal-sparing extended posterior approach may be able to achieve similar patient-reported and gait outcomes with those of primary THA within the first 12 postoperative months.